Studentsâ Extracurricular Activities in Higher Education and Its Effect on Personal Development and Academic Achievement (Case Study In Islamic State University of Suska Riau) - Diniaty, Amirah; Kurniati, Annisa (Institut Agama Islam Negeri Imam Bonjol Padang, 2014)
This study investigates the studentsâ extracurricular activities at Islamic State University of Suska Riau concerning the types and forms of their activities, background of the activity, benefits of extracurricular activities, and its effect on studentsâ self-development and academic achievement. 300 students who enroll at sixth semester in eight Faculties (Tarbiyah and Teacherâs Training, Sharia and Law, Ushuludin, Dakwah and Communication Sciences, Science and Technology, Psychology, Economics and Social Sciences, Agriculture and Animal Husbandry) were the sample of this study. The data were then processed statistically using percentages and regression of correlation. It was found that the type of extracurricular followed by the students were leadership (70%), those of whom had the motivation to add insight, knowledge and more critical thinking were (44.67%). Some students followed extra-curricular activity because of their solicitation or to follow the main stream (37%), some students did not get financial benefits from the activity (34.67%). Some other respondents felt that they could follow the extracurricular talents, interests and personal abilities (58.67%), and think about their future after graduating from the college (66%). Things need to be followed up by students and university staffs were the more active students who attend the extracurricular activities were the lower achievement ones.Â Copyright Â© 2014 by Al-Talim All right reserved